Rapid identification and simultaneous analysis of multiple constituents from Rheum tanguticum Maxim. ex Balf. by UPLC/Q-TOF-MS. Issue 13 (3rd July 2017) - Gao, Liang-Liang; Guo, Tao; Xu, Xu-Dong; Yang, Jun-Shan
Abstract: Rhubarb contains biologically active compounds such as anthraquinones, anthrones, stilbenes and tannins. A rapid and efficient UPLC/Q-TOF-MS/MS method was developed and applied towards identifying the constituents of Rheum tanguticum Maxim. ex Balf. for the first time. Chemical constituents were separated and investigated by UPLC/Q-TOF-MS/MS in the negative ion mode. The ESI-MS 2 fragmentation pathways of four types of compounds were interpreted, providing a very useful guidance for the characterisation of different types of compounds. Based on the exact mass information, fragmentation characteristic and LC retention time of 7 reference standards, 30 constituents were tentatively identified from the methanol extract of R. tanguticum . Among them, seven compounds were described for the first time from R. tanguticum and two from the genus Rheum were described for the first time. The analytical tool used here is valuable for the rapid separation and identification of multiple and minor constituents in methanol extracts of R. tanguticum . Graphical Abstract: